2019
DOI: 10.1259/dmfr.20190039
|View full text |Cite
|
Sign up to set email alerts
|

Cone beam CT imaging of the mandibular third molar: a position paper prepared by the European Academy of DentoMaxilloFacial Radiology (EADMFR)

Abstract: Objectives: Lack of evidence on the use of CBCT for management of mandibular third molars in Radiation Protection guideline no. 172 of the European Commission made the European Academy of DentoMaxilloFacial Radiology (EADMFR) decide to update the recommendations of the guideline. Methods and materials: A literature search was performed addressing the following questions: (1) does CBCT change the treatment of the patient?; (2) does CBCT reduce the number of post-operative sensory disturbances of the inferior al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 25 publications
1
36
0
5
Order By: Relevance
“…CBCT has been found to be superior for cases which demand images in three planes, for instance, Guerrero et al [3] found that CBCT images improved scores for subjective image quality and surgical confidence levels when estimating the length of implants at posterior locations of the jaws. However, studies have also concluded that CBCT investigations are not always necessary in order to give a high diagnostic accuracy and a high benefit for the patients [7,13,14]. The backside is that the radiation dose to the patient is higher than with intraoral imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CBCT has been found to be superior for cases which demand images in three planes, for instance, Guerrero et al [3] found that CBCT images improved scores for subjective image quality and surgical confidence levels when estimating the length of implants at posterior locations of the jaws. However, studies have also concluded that CBCT investigations are not always necessary in order to give a high diagnostic accuracy and a high benefit for the patients [7,13,14]. The backside is that the radiation dose to the patient is higher than with intraoral imaging.…”
Section: Discussionmentioning
confidence: 99%
“…The European Commission has established guidelines and regulations [4] for CBCT use in European Union (EU) member countries. Studies have evaluated various CBCT examinations to verify the need for this technique [5][6][7]. Studies have also investigated CBCT units from various manufacturers to measure radiation doses to patients.…”
Section: Introductionmentioning
confidence: 99%
“…1). 15,17 Impacted Maxillary Third Molars Using CBCT for treatment planning of impacted maxillary third molars has been analyzed in different studies, but the latest retrospective study conducted by a team of experienced oral and maxillofacial radiologists concluded that a CBCT examination is indicated when external root resorption of the second molar is suspected on panoramic radiography. Hermann et al reported that CBCT findings regarding the second maxillary molar's severe root resorption (►Fig.…”
Section: Impacted Mandibular Third Molarsmentioning
confidence: 99%
“…New evidence-based recommendations advocate that CBCT imaging of third molars should not be used routinely before their removal and should only be used when a specific clinical question cannot be answered by conventional (panoramic and/ or intraoral) imaging alone. 5 In a scenario like Figure 1, however, could a DPT be bypassed in favour of CBCT when possible caries is observed on the second molar? From this, we could assess the presence or absence of a distal radiolucency in the second molar, alongside all the conventional information CBCT provides for treatment planning, without the need for an intermediary DPT.…”
mentioning
confidence: 99%
“…We need to define the 'optimum' time for treatment -either at time of presentation or even before any damage being caused. 5 While this creates a dilemma regarding the patient with an unrestored dentition and good oral hygiene, what about individuals with moderate to increased caries risk? Should a patient's overall oral health be taken into account when considering extraction of impacted lower third molars?…”
mentioning
confidence: 99%